2018
DOI: 10.1002/hed.25495
|View full text |Cite
|
Sign up to set email alerts
|

Three prognostic indexes as predictors of response to adjuvant chemoradiotherapy in patients with oral squamous cell carcinoma after radical surgery: A large‐scale prospective study

Abstract: Background To develop and validate practical prognostic indexes (PIs) for predicting the prognosis and response to postoperative adjuvant therapy in patients with oral squamous cell carcinoma (OSCC). Methods A large cohort of 1071 OSCC patients were randomized to either training set (N = 708) or validation set (N = 363). Three types of PIs were developed according to the nomogram scores, β coefficients and excess hazard ratios, respectively. Restricted cubic spline was used to demonstrate the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…Chemotherapy is an important treatment for oral cancer patients. However, several previous studies found that chemotherapy was not associated with improved prognosis of oral cancer [31]. Hence, whether all patients should be recommended for chemotherapy is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is an important treatment for oral cancer patients. However, several previous studies found that chemotherapy was not associated with improved prognosis of oral cancer [31]. Hence, whether all patients should be recommended for chemotherapy is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Although several nomograms have been described for oral SCC, [21][22][23][24][25][26] attempts at devising a nomogram for OTSCC alone have been limited. Li and colleagues used data from the SEER database on 12 674 patients to design such a nomogram including the variables age, race, marital status, TNM stage and tumor grading.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence obtained from epidemiological studies has shown that systemic inflammatory markers based on circulating blood cell, such as the neutrophil‐to‐lymphocyte ratio (NLR), lymphocyte‐to‐monocyte ratio (LMR), and platelet‐to‐lymphocyte ratio (PLR), were related to the survival outcome of patients with OSCC 5‐7 . Meanwhile, compared with the traditional AJCC staging system, the nomogram combined with biomarkers of systemic inflammatory response could predict the prognosis of OSCC more accurately 8‐10 …”
Section: Introductionmentioning
confidence: 99%